SOSIALISASI TIPS DAN TRIK MENYUSUN KARYA TULIS ILMIAH - Sutrisno Sutrisno; made irma lestari (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2022)
The purpose of this activity is to provide understanding to final year students about writing scientific articles from theses and theses for students and how to publish them in accredited and unaccredited national journals as a condition for attending the final trial or graduation requirements. This activity is also a means to motivate students to write quality scientific articles from the results of theses and theses. The method of implementing this Community Service (PKM) activity uses the lecture and demonstration method. This activity was carried out through Zoom Meetings and Live Streaming YouTube. This activity involved 2 lecturers of the Wiyatamandala School of Economics, namely Mrs. Made Irma Lestari S.E, M.Acc and Mr. Drs. Sutrisno M.M. The number of participants involved in this community service activity (PKM) are dozens of participants consisting of final year students of the Wiyatamandala School of Economics in the final semester who will face a thesis trial as well as various other students from universities and colleges in Jakarta and its surroundings. The topic of the first material is